Place names of color designation in Tuvan language - Suvandii, Nadezhda D. (The New Research of Tuva, 2019)
The article systematizes the place names of Tuva which contain a Tuvan word referencing any of the colors. The source material was collected by the author during linguistic and dialectological expeditions to various rayons of the Republic of Tuva in 1999-2019: in Verkhneusinskoye, Yermakovsky rayon, Krasnoyarsk Krai an in Khovd and Bayan-Ölgii aimags of Western Mongolia. The list also includes place names recorded and published in earlier research literature. An analysis of color designations in the toponymical system of Tuvan language shows that the place names containing the lexemes ‘ak’ (white), ‘kara’ (black), ‘saryg’ (yellow), ‘kyzyl’ (red), ‘nogaan’ (green) and ‘kөk’ (blue) are quite numerous. This is a common feature in toponymies of all Turkic languages. It also reflects the color characteristic of geographical objects and natural landscapes in the areas populated by Tuvans. In terms of linguistic structure, toponyms designating color are compounds which typically include a color-indicating adjective and a noun. This model provides a color characteristic of a geographical name, especially referring to the color of rock, lakes, rivers and vegetation.